Water transport due to wick action through concrete - Aldred, James M. (Curtin University, 2008)
Wick action is the transport of water through a concrete element from a face in contact with water to a drying face as occurs in basements, tunnels, slabs on grade and hollow offshore structures. Water transport through concrete due to wick action is many times greater due to pressure permeability under typical environmental conditions. Therefore wick action plays an important role in the watertightness and durability of concrete structures. Current models of wick action are based on an equilibrium developing between the rate of water entering concrete by sorptivity and leaving by water vapour diffusion where initial moisture content should not change the steady state rate, only the dominant factor in the early stages.Wick action tests were conducted on concrete specimens of varying initial moisture condition, thickness, orientation and composition over periods ranging up to 450 days. Some wick action tests were conducted at 50% and 75% relative humidity and using a penetrating solution of reduced surface tension. The rate of wick action was found to be inversely proportional to thickness regardless of the initial moisture content of the specimen. Initial saturation was found to significantly increase wick action and moisture flow in ordinary Portland cement (OPC) and hydrophobic (HI) concretes drying at 75% RH and HI concrete drying at 50% RH. The data are consistent with the well documented hysteresis between sorption/desorption isotherms. Concretes containing silica fume (SF) and ground granulated blast-furnace slag (GGBS) did not exhibit such hysteresis. Reducing the surface tension of the pentrating solution profoundly reduced the sorptivity into dried specimens but not the depth of penetration or the steady state wick action rate. Direct measurements on osmotic flow through vacuum saturated specimens showed that osmotic effects had a limited effect on wick action at salt concentrations expected in most environmental conditions.The research demonstrates that desorptivity from the drying surface rather than sorptivity into the wetting surface is the dominant factor determining wick action through concrete. The ease with which desorptivity can be measured and the simple empirical model developed provides practicising engineers with a useful tool to estimate water transport due to wick action through concrete in partially immersed conditions.